Meningkatkan Minat Baca Anak Melalui Kegiatan Perpustakaan Keliling Di Taman Bacaan Masyarakat - Muhammad Rafli Alviansyah; Muthia Fithri Sabila; Nastiti Novitasari; Zamzam Holfinur; Meta Hendrayani; Riezki Akbar Maulana; Andra Nata; Al Fikri Syahputra (Pusat Riset dan Inovasi Nasional, 2023)
This devotion aims to investigate the effectiveness of the activities of the Ampar Buku through the library around in growing reading interest in children in the Community Reading Center. The method of implementation used in the activities of the community to the community is with a participatory approach. The program results show that the activities of the Ampar Buku through the bookmobile have a positive impact in increasing reading interest in children. Children show high enthusiasm to this activity and look more active and excited when the activity is implemented. In conclusion, the activities of the Ampar Buku through the bookmobile has great potential in increasing children's interest in the reading of the Community Reading Center and also recommends to expand and continue the program to achieve a significant impact in the development of child literacy.